Thrombomodulin as a Physiological Modulator of Intravascular Injury - Watanabe-Kusunoki, Kanako; Nakazawa, Daigo; Ishizu, Akihiro; Atsumi, Tatsuya (Frontiers in Immunology, 2020)
Thrombomodulin (TM), which is predominantly expressed on the endothelium, plays an important role in maintaining vascular homeostasis by regulating the coagulation system. Intravascular injury and inflammation are complicated physiological processes that are induced by injured endothelium-mediated pro-coagulant signaling, necrotic endothelial- and blood cell-derived damage-associated molecular patterns (DAMPs), and DAMP-mediated inflammation. During the hypercoagulable state after endothelial injury, TM is released into the intravascular space by proteolytic cleavage of the endothelium component. Recombinant TM (rTM) is clinically applied to patients with disseminated intravascular coagulation, resulting in protection from tissue injury. Recent studies have revealed that rTM functions as an inflammatory regulator beyond hemostasis through various molecular mechanisms. More specifically, rTM neutralizes DAMPs, including histones and high mobility group box 1 (HMGB1), suppresses excessive activation of the complement system, physiologically protects the endothelium, and influences both innate and acquired immunity. Neutrophil extracellular traps (NETs) promote immunothrombosis by orchestrating platelets to enclose infectious invaders as part of the innate immune system, but excessive immunothrombosis can cause intravascular injury. However, rTM can directly and indirectly regulate NET formation. Furthermore, rTM interacts with mediators of acquired immunity to resolve vascular inflammation. So far, rTM has shown good efficacy in suppressing inflammation in various experimental models, including thrombotic microangiopathy, sterile inflammatory disorders, autoimmune diseases, and sepsis. Thus, rTM has the potential to become a novel tool to regulate intravascular injury via pleiotropic effects.